Associations of segment-specific pulse wave velocity with vascular calcification: the Atherosclerosis Risk in Communities (ARIC) Study. (3rd October 2022) - Ejiri, K; Ding, N; Kim, E; Honda, Y; Cainzos-Achirica, M; Tanaka, H; Howard-Claudio, C; Butler, K; Hughes, T; Coresh, J; Van't Hof, J; Meyer, M; et al.
Abstract: Background: Pulse wave velocity (PWV) is a non-invasive measure of arterial stiffness and a predictor of cardiovascular disease (CVD). Vascular calcification, especially coronary artery calcium (CAC) measured by computed tomography (CT), is one of the strongest predictors of CVD but requires radiation for measurement. PWV may be helpful to identify persons with vascular calcification who may benefit from formal assessment of vascular calcification with CT. However, the associations between PWV and vascular calcification across different vascular beds have not been fully investigated. Purpose: The aims of this study were to quantify the association between PWV and calcification at different segments and to explore whether PWV can identify individuals with vascular calcification beyond traditional risk factors. Methods: Among 1486 ARIC Study participants (mean age 79.3 [SD 4.2] years), we measured PWV by OMRON VP1000plus at the following segments: heart-carotid (hcPWV), heart-femoral (hfPWV), carotid-femoral (cfPWV), heart-ankle (haPWV), brachial-ankle (baPWV) and femoral-ankle (faPWV). Participants were stratified into four groups based on quartiles of each PWV measure. Dependent (i.e., outcome) variables were high calcium score (≥75th percentile of Agatston score by CT) of the following vascular beds (including valves): coronary arteries, aortic valve ring, aortic valve, mitral valve, ascending aorta, and descending aorta. We ran multivariable logistic regression models and assessed c-statistics as a measure of prediction discrimination. Results: Only cfPWV was significantly positively associated with high CAC (adjusted odds ratio [OR] for the highest vs. lowest quartile: 1.73 [95% CI: 1.17–2.55]) (green dot in figure). The associations were overall most evident for descending aorta calcification, with significantly positive results for hfPWV (gold dot in figure), cfPWV (green dot), haPWV (emerald dot), and baPWV (blue dot). For example, adjusted OR for the highest vs. lowest quartile of cfPWV was 4.08 (2.70–6.24). hfPWV and cfPWV were significantly associated with mitral valve calcification as well. In contrast, faPWV (purple dots) was inversely associated with calcification of aortic valve ring, ascending aorta, and descending aorta. For descending aorta calcification, even the second highest quartile of the following measures demonstrated significant adjusted OR: hfPWV (3.21 [2.11–4.95]), cfPWV (2.11 [1.40–3.20]), and baPWV (1.75 [1.14–2.69]). Simultaneously adding cfPWV and hfPWV improved c-statistic for CAC (Δc-statistic 0.011 [0.0007–0.022]) and descending aorta calcification (0.035 [0.017–0.053]). Conclusions: The associations of PWV with vascular calcification varied substantially across segments, with descending aorta calcification most closely linked to PWV measures and cfPWV most robustly associated with calcification of multiple vascular beds. cfPWV and hfPWV, together, improved discrimination of high CAC beyond traditional risk factors. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The National Heart, Lung, and Blood Institute, National Institutes of Health